Bi-cephalic parietal and cerebellar direct current stimulation interferes with early error correction in prism adaptation: Toward a complex view of the neural mechanisms underlying visuomotor control. (December 2018) - Panico, Francesco; Sagliano, Laura; Grossi, Dario; Trojano, Luigi
Abstract: Prism Adaptation (PA) represents a valid tool to assess short-term visuomotor plasticity. Two adaptive processes are involved during PA: recalibration, contributing to early error compensation, and spatial realignment, contributing to after-effect development. Classical models on PA posit that adaptive mechanisms underlying PA rely on segregated regions in the brain. Indeed, they ascribe recalibration to the activity of the Posterior Parietal Cortex (PPC) and spatial realignment to the activity of the Cerebellum. The present experiment challenges the idea of a clear-cut separation of the role of the brain areas involved in PA, proposing an interpretation in terms of interrelated brain regions. To this purpose we interfered with the activity of the PPC and the Cerebellum by means of complementary protocols of stimulation. Bi-cephalic transcranial Direct Current Stimulation was delivered simultaneously on the PPC and the Cerebellum during PA in two groups of participants receiving real stimulation with opposite polarities (anode on PPC and cathode on Cerebellum or vice-versa) and in a control group (Sham stimulation). Differences in mean errors between groups were analyzed. Results show that the two groups of real stimulation exhibited larger displacements in early error compensation compared to the Sham Group, but they did not differ from each other. No group difference was found in late error compensation and after-effect. In conclusion, the present findings provide the first direct evidence that a brain circuit connecting the PPC and the Cerebellum is involved in early stages of visuomotor adaptation, and pave the way for updating classical models of PA.